i-Solat Sunat (i-SS) - I. Mohd Faizul;; Y. Norhasna;; N. Hartini;; A. Ahmad Yazid; (Universiti Sains Islam Malaysia, 2024)
This project is a courseware about the collections of solat-solaf sunat, and a basic of doa'. It's suitable in all the type of age. The purpose of this courseware is to expose the knowledge about Islamic religion and we are focuses on the solat sunat and basic of the doa. Besides that, this courseware also gives the information in effective and attractive which who want to use it. In addition, this courseware is applied in information technology as a medium. This courseware also have three languages in Malay, English and Arabic as a reason this courseware in multi languages because make a users easy in accesses this courseware. The software are used in this courseware is flash, adobe, sound forge and others. Furthermore, the others reference that we are use in build this courseware is from the book, internet, magazines and others.